2012
DOI: 10.1183/09031936.00168811
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired pneumonia in outpatients: aetiology and outcomes

Abstract: The purpose of this study was to establish the microbial aetiology and outcomes of patients with community-acquired pneumonia (CAP) treated as outpatients after presenting to a hospital emergency care unit.A prospective observational study was carried out in the Hospital Clinic of Barcelona (Barcelona, Spain). All consecutive cases of CAP treated as outpatients were included.568 adult outpatients with CAP were studied (mean¡SD age 47.2¡17.6 yrs; 110 (19.4%) were aged o65 yrs). Aetiological diagnoses were estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 29 publications
3
59
1
1
Order By: Relevance
“…However, there is little information regarding the prevalence and clinical impact of bacteraemia in CAP patients treated outside the hospital. Previous studies reported incidences of 2.1-7%, respectively [5][6][7][8]. However, few data exist regard predictive factors and the clinical outcomes associated with positive blood cultures in this population [8].…”
Section: Bacteraemia In Outpatients With Community-acquired Pneumoniamentioning
confidence: 86%
“…However, there is little information regarding the prevalence and clinical impact of bacteraemia in CAP patients treated outside the hospital. Previous studies reported incidences of 2.1-7%, respectively [5][6][7][8]. However, few data exist regard predictive factors and the clinical outcomes associated with positive blood cultures in this population [8].…”
Section: Bacteraemia In Outpatients With Community-acquired Pneumoniamentioning
confidence: 86%
“…In a recent study of CAP aetiology in outpatients, Streptococcus pneumoniae was reported to be the most frequent pathogen [1]; unchanged from previous studies. The knowledge that S. pneumoniae is the commonest cause is sufficient to assist the choice of appropriate antibiotics; the most important management decision required for most patients.…”
mentioning
confidence: 81%
“…In the outpatient setting nonresponse was much lower, ranging from 2.3% [Cilloniz et al 2012] to 7.5% [Fantin et al 2001] or 8% [Minogue et al 1998]. In all these studies, mortality rate was below 5% and appeared to be mainly related to the patient's comorbidities and not to antibiotic selection or to pneumonia itself [Minogue et al 1998;Fantin et al 2001;Cilloniz et al 2012].…”
Section: Assessing Nonrespondersmentioning
confidence: 96%
“…In all these studies, mortality rate was below 5% and appeared to be mainly related to the patient's comorbidities and not to antibiotic selection or to pneumonia itself [Minogue et al 1998;Fantin et al 2001;Cilloniz et al 2012].…”
Section: Assessing Nonrespondersmentioning
confidence: 99%
See 1 more Smart Citation